When Students Say Far Too Much: Examining Gushing in the ELT Classroom - Gerrard Mugford; Oscar Ramírez Cuevas (Universidad Nacional de Colombia, 2015)
English foreign-language users often overuse words when faced with difficult situations. Called gushing, such excessive use of words is often legitimately employed by native speakers to express, for instance, gratitude and apologies when a simple thank you or sorry does not sufficiently convey an interlocutor's feelings. This paper examines the appropriateness and effectiveness of gushing when employed by advanced students facing difficult situations. Answering discourse completion tasks, students from a private university in Guadalajara, Mexico were asked to employ acquiescing, persisting, and aggressing strategies to resolve two particular situations. The results indicate that gushing was widely used, but in communicatively ineffective ways, reflecting an area where teachers can help develop students' communicative competencies.